The vitae of Bodleian Library Ms Douce 114 - Vander Veen, Brian C. (2007)
Bodleian Library MS Douce 114 contains the unique copy of four Middle English texts, translations of Latin vitae, all describing Continental women saints whose unusual forms of devotion set them apart from the often more sober atmosphere of late-medieval English spirituality in which the texts appeared. The texts first attracted scholarly notice following the publication of The Book of Margery Kempe and the subsequent interest in the lives of the Continental women mystics whom Kempe resembled far more than her own English contemporaries; however, the texts have yet to be examined in any detail. This study investigates both the physical production of the translation and the context of book production in which the manuscript appeared, as well as the ideological context and controversies which would have informed the reading and reception of the texts.